Calcification of the alar ligament mimics fracture of the craniovertebral junction (CVJ): an incidental finding from computerised tomography of the cervical spine following trauma - Che Mohamed, Siti Kamariah; Abd. Aziz, Azian (Universiti Sains Malaysia Press., 2009)
When performing a radiological assessment for a trauma case with associated head injury, a fragment of dense tissue detected near the craniovertebral junction would rapidly be assessed as a fractured bone fragment. However, if further imaging and evaluation of the cervical spine with computerised tomography (CT) did not demonstrate an obvious fracture, then the possibility of ligament calcification would be considered. We present a case involving a previously healthy 44-year old man who was admitted following a severe head injury from a road traffic accident. CT scans of the head showed multiple intracrania haemorrhages, while scans of the cervical spine revealed a small, well-defined, ovoid calcification in the right alar ligament. This was initially thought to be a fracture fragment. Although such calcification is uncommon, accident and emergency physicians and radiologists may find this useful as a differential diagnosis in patients presenting with neck pain or traumatic head injury.